2022
DOI: 10.3389/fpubh.2022.921953
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of potential risk factors associated with COVID-19 and hospitalization

Abstract: Coronavirus disease 2019 (COVID-19) was found to cause complications in certain groups of people, leading to hospitalization. Several factors have been linked to this, such as gender, age, comorbidity, and race. Understanding the precise reasons for the COVID-19-induced complications might help in designing strategies to minimize hospitalization. A retrospective, cross-sectional observational study was conducted for patients in a COVID-19-designated specialty hospital after obtaining ethical clearance. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…This is a retrospective study with two groups of patients that received CCP: Group A, formed by patients that received compassionate CCP, from January to May 2021, n = 94, and Group B formed by patients from a previous clinical study, from March to October 2020, n = 47. Most of the participants were male, with mean age above 60 years and with comorbidities, a population under higher risk of hospitalization and ICU admission [14]. Group B was different from group A in that group B had a higher percentage of patients in ICU on the day of transfusion and a higher WHO ordinal scale on Day 0, suggesting more severity.…”
Section: -Discussionmentioning
confidence: 97%
“…This is a retrospective study with two groups of patients that received CCP: Group A, formed by patients that received compassionate CCP, from January to May 2021, n = 94, and Group B formed by patients from a previous clinical study, from March to October 2020, n = 47. Most of the participants were male, with mean age above 60 years and with comorbidities, a population under higher risk of hospitalization and ICU admission [14]. Group B was different from group A in that group B had a higher percentage of patients in ICU on the day of transfusion and a higher WHO ordinal scale on Day 0, suggesting more severity.…”
Section: -Discussionmentioning
confidence: 97%
“…Retrospective studies from China have found that the mortality rate of critically ill COVID-19 patients can reach 38-62% 14 , 15 . Previous studies have shown that factors such as male, older age, comorbidities, medical history, white blood cell count, serum creatinine, C-reactive protein, and erythrocyte sedimentation rate increase the hospitalization and mortality rates of COVID-19 patients 16 - 20 . However, the risk factors for mortality and CVD in MHD patients after COVID-19 infection require further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…Although the prevalence of COVID-19 can be reduced, COVID-19 vaccination in PH children does not reduce the severity, number and distribution of symptoms in COVID-19 disease. Several studies have explored factors influencing the severity of COVID-19 disease ( 2 , 23 , 24 ). The most important influencing factor is the presence of severe comorbidities.…”
Section: Discussionmentioning
confidence: 99%